2018
DOI: 10.14260/jemds/2018/1204
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Fractional Co2 Laser Treatment for the Treatment of Overactive Bladder Syndrome in Menopausal Women- A Three Month Pilot Study

Abstract: BACKGROUND Overactive bladder syndrome (OABS) is a common disorder that encompasses urgency, frequency, and nocturia. Various methods of therapies have been utilized worldwide. Despite progresses, it remains a formidable challenge. Laser treatment has emerged to reliably treat the symptoms complex. This study was intended to evaluate the effect of fractional CO2 laser on the main symptoms of OABS. MATERIALS AND METHODS A prospective pre-and post-intervention pilot study was conducted on 31 female subjects recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…After reviewing the full‐text articles, an additional 20 records were excluded. This process resulted in 49 articles, 1,2,4,13‐58 which were further reviewed using a hand‐searching approach. Table 2 displays all the selected studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After reviewing the full‐text articles, an additional 20 records were excluded. This process resulted in 49 articles, 1,2,4,13‐58 which were further reviewed using a hand‐searching approach. Table 2 displays all the selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 displays all the selected studies. Of these, 37 were about the CO 2 laser, 1,2,4,13,14,17‐19,22‐27,29‐31,33‐37,39,42,45‐47,49‐58 10 were about the Erbium laser, 15,16,20,32,38,40,41,43,44,48 and two were about radiofrequency 21,28 . Outcomes of the studies included in the systematic review are shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…27,33 Mohajeri et al offered women with OAB laser treatment, and also reported that their sexual function was not improved (PISQ-12). 54 Alkhafajy and Alyaseen observed improved sexual function using a subjective three-grade scale in women with vaginal relaxation (P = 0.004). 26 In one study in women with GSM there was a significant improvement in FSFI scores in all participants (P < 0.001) 53 and in another in 35 out of 40 participants (P < 0.001).…”
Section: Sexual Functionmentioning
confidence: 95%
“…28 There were three other GSM studies in which women with unspecified incontinence were included showing significant improvement on the ICIQ-UI SF scores at 4 weeks of follow up (P < 0.001) 42 and 12 months of follow up (P < 0.001), 53 as well as a satisfaction rate of 75%. 43 Three studies addressed urge incontinence primarily, 31,54,55 but in combination with GSM in one. 55 A significant improvement in the ICIQ-OAB score was measured after the first treatment (P < 0.05) 54 and lasted up to 30 days post treatment (P < 0.0001).…”
Section: Urinary Incontinencementioning
confidence: 99%
See 1 more Smart Citation